Structure of the arbustive-arbory community in Subcaducifolia Tropical Forests (Research, Society and Development, 2020)
The objective was to characterize the structure of the shrub-tree community in Seasonal Semideciduous Forests (FES) seeking to investigate the richness and the similarity of species between the areas. Three environments were evaluated in a Permanent Preservation Area: FES Submontana; Alluvial FES and Secondary Vegetation Area (AVS). Through the contiguous plot method, individuals with CAP equal to or greater than 10 cm / 1.30 m from the soil were identified. For data analysis, NMDS ordering based on the Bray-Curtis dissimilarity matrix, cluster analysis (UPGMA), Venn diagram, alpha diversity and phytosociological parameters (Dr, DoR, FR, IVI, IVC). A total of 2,780 individuals were registered. The sampled areas resulted in three environments significantly different in terms of community structure (Pillai = 1.25; df = 4 and 294; p